CHALLENGES AND MARKETING SOLUTIONS TO SUPPORT THE ROLE OF SONGKET FABRIC SMES IN WELCOMING THE ERA OF SOCIETY 5.0 - Wijaya, Septihani Michella; Metty, Patrice Febiyani; Yukianti, Chiara Rizka; Ie, Mei (International Journal of Application on Economics and Business, 2023)
The more efforts are made, the more the country's economy will increase. The country's economy is increasing thanks to a significant increase in GDP (Gross Domestic Product) every year. MSMEs of songket cloth are one of the drivers of the country's economy because songket cloth has strength as the main advantage, namely that MSMEs can absorb jobs and grow the local community's economy. The right strategy for the MSME sector is to grow and build, consisting of market penetration to increase market share by using products already on the market. Market development is to increase market share in new markets by using existing products, and product development aim to increase market share by creating new products or developing existing products. Based on these leading concerns, the team has conducted a series of analyzes and formulated the right marketing strategy, namely the SMEs Bazaar with the theme "The Future of SMEs", Integrated Marketing Communication – Scan QR Code, E-commerce Partnership, show with SMEs with the theme "Custom Made to Fit ur Desire", and Empowerment SMEs Program. This strategy is believed to be effective and efficient in improving the performance of songket SMEs in Indonesia. With the development of technology and digitalization, Sasirangan Fabric products produced by SMEs can be sold using digital platforms such as e-commerce to make it easier for the public to reach and help in the expansion process to enter the global market. However, the limited internet penetration of MSME actors is a major problem in digital transformation. Therefore, it is necessary to analyze how this type of MSME can improve Indonesia's digital economy and welcome the era of society 5.0.